2019
DOI: 10.15406/aovs.2019.09.00349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of color vision and contrast sensitivity in diabetic patients without retinopathy

Abstract: Purpose: The purpose of this study is to evaluate the color vision and contrast sensitivity in diabetic patients without diabetic retinopathy, and to assess the color vision and contrast sensitivity in every diabetic patient before the occurrence of diabetic retinopathy and make it an integral part of routine examination. Materials and methods: A hospital based descriptive cross-sectional study was conducted at Aziz-Fatimah Hospital Faisalabad including 50 patients of age between 30 to 55 years. Information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…In the present study, no significant association was found between diabetes and diabetic retinopathy with CVD. This is while most previous studies reported CVD in a high percentage of patients with diabetes, whether in the presence [36] or absence of diabetic retinopathy [37] . For example, Tan et al [38] , observed that one in four patients with diabetes had CVD, with tritanomaly being the most common form of CVD in these patients.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, no significant association was found between diabetes and diabetic retinopathy with CVD. This is while most previous studies reported CVD in a high percentage of patients with diabetes, whether in the presence [36] or absence of diabetic retinopathy [37] . For example, Tan et al [38] , observed that one in four patients with diabetes had CVD, with tritanomaly being the most common form of CVD in these patients.…”
Section: Discussionmentioning
confidence: 65%
“…These alterations include the loss of the ganglion cell complex or microvascular abnormalities [ 6 , 7 ]. In addition to anatomical changes, functional defects have been observed through other examinations such as microperimetry [ 8 , 9 ], contrast sensitivity [ 10 ] and colour perception tests [ 11 , 12 ]. Electrophysiological abnormalities are common findings in long-standing type 1 diabetic (T1DM) patients with no signs of DR.…”
Section: Introductionmentioning
confidence: 99%